100 GHz transformer‐coupled quadrature oscillator. Issue 4 (1st February 2013) - Lin, K.‐T.; Chen, H.‐K.; Lu, S.‐S.
Abstract : A 96.4–100.8 GHz quadrature oscillator utilising transformer‐coupled and magnetic tuning techniques has been implemented in 90 nm CMOS technology. Under 1 V supply operation, experimental results show that the phase and amplitude error between I and Q paths are smaller than 1.6° and 0.9 dB with power dissipation from 8.7 to 21 mW. The measured phase noise is − 110.4 dBc/Hz at 10 MHz‐offset away from the downconverted 98.6 GHz carrier. This oscillator occupies a chip area of 0.357 mm 2 .